Assessment of Frequency of Polypharmacy along with its Relation to Dementia and Drug Adherence among Admitted Geriatric Patients in Medicine Wards of a Tertiary Care Hospital - Khatun, Ummay Fatema; Dey, Subrata; Paul, Sujat; Kabir, Sheikh Khairul; Dev, Aparna (Journal of Medicine, 2023)
Background: Polypharmacy has been associated with adverse drug reactions, medication errors and non- adherence to prescribe drugs and geriatric population is more prone to this condition. On the other hand, dementia is a major concern among growing chronic diseases in the ageing society and its assessment has not been adequately done in our setting. Method: One hundred subjects aged more≥60 years were included in this analytical cross-sectional from the Medicine Department of Chattogram Medical College Hospital from November 2018 to April 2019. A structured case record form collected data, and drug adherence were measured by Morisky Medication Adherence Scale-8 (MMAS-8). PP was defined as intake of e”5 drugs. Cognitive impairment was classified as presence or absence of dementia by Mini-cog tool. Results: The average age of individuals was 65.56±6.9 years and 62 were men. The prevalence of polypharmacy, dementia, and drug non-adherence was respectively, 56%, 47%, and 49%. Patients with polypharmacy were more likely to be non-adherent (odds ratio: 2.4; 95% CI: 1.1-5.4; p=0.039) and demented (odds ratio: 3.38; 95% CI: 1.1-11.8; p=0.019) than the elderly patients without polypharmacy. Conclusion: As there is significant association between polypharmacy with dementia and drug nonadherence, judicious use of drugs is mandatory to reduce these risk. J MEDICINE 2023; 24: 3-9